Factors associated with awareness, reading and perceptions of clinical practice guidelines among the general population in Japan: A nationwide cross-sectional survey (INFORM Study 2023) - Yosuke Hatakeyama; Akiko Yaguchi-Saito; Kanako Seto; Ryo Onishi; Ryosuke Hayashi; Koki Hirata; Kunichika Matsumoto; Tomonori Hasegawa; Yoshimitsu Takahashi; Takeo Nakayama; Junko Saito; Aki Otsuki; et al. (PLoS ONE, 2026)
Background Clinical Practice Guidelines (CPGs) support evidence-based, shared decision-making by providing recommendations based on the best available evidence, including systematic reviews, clinical trials, and expert consensus. Despite their potential to improve the quality of healthcare and reduce unnecessary interventions, CPGs remain inadequately disseminated and implemented. Key barriers include limited awareness and poor perception among patients and the general public. To inform strategies to improve CPG dissemination, this study aimed to investigate the association between socioeconomic factors and the awareness, reading, and perceptions of CPGs among the Japanese general population. Methods A nationwide cross-sectional anonymous mail survey (INFORM Study 2023) was conducted among 10,000 randomly selected Japanese adults aged ≥20 years using stratified two-stage random sampling. This study was conducted as part of the INFORM Study 2023, with items related to CPGs included as an approved module. Logistic regression models were used to identify respondent characteristics associated with the awareness and reading experience of CPGs, and to assess the association between reading CPGs and eight perceptions held about them. Results The response rate was 35.3% (n = 3,452). After excluding cases with missing data on CPG awareness, the remaining responses were included in the analysis (n = 3,343). Among these, 82.5% were unaware of CPGs, 9.9% were aware of CPGs but had never read one, and 7.6% were aware of CPGs and had read one. Awareness was significantly higher among individuals with higher education (adjusted odds ratio [aOR]: 2.060 for vocational school; 1.813 for university graduates), higher household income (aOR: 1.882 for ≥8 million yen), excellent health (aOR: 1.373), and frequent healthcare visits (aOR: 1.741 for ≥10 visits/year). Household size of ≥2 members (aOR: 0.591) was associated with lower awareness. Reading CPGs was associated with a self-history of cancer (aOR: 1.858). Of eight perceptions, respondents who had read CPGs correctly disagreed with the notion that CPGs harm patient-provider relationships. Among other respondents, misconceptions about CPGs persisted, particularly regarding their limitations and recommendations. Conclusions Among the general population in Japan, awareness of CPGs is associated with demographic and socioeconomic characteristics. Tailored dissemination strategies—particularly for individuals with lower income or education levels and other groups identified in this study—are essential to improving awareness and supporting informed healthcare decision-making. These findings also highlight the need to integrate CPG literacy into national health education initiatives to enhance public access to evidence-based care.